2019
DOI: 10.1111/jnu.12501
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Depression and Frailty in Community‐Dwelling Older People: A Systematic Review and Meta‐Analysis of 84,351 Older Adults

Abstract: Objectives In this study we investigated the correlation between depression and frailty in older adults. Additionally, correlations among study designs (prospective vs. cross‐sectional), regions, depression indices, frailty indices, covariance corrections, and sexes were explored to support the analysis. Methods A systematic literature review and meta‐analysis were conducted. A total of 84,351 older adults, all 65 years of age or older, were analyzed. Both authors independently extracted and examined retrieved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
64
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(92 citation statements)
references
References 34 publications
8
64
0
8
Order By: Relevance
“…The possible explanation could be that older people who had been living in a private institution (more expensive in the metropolitan areas than public institution) usually have higher social economic status; they were more likely to feel lonely [30] and loss of appetite [31] when staying away from family and changing their ways of previous life, resulting in higher likelihood of being frailer. Compared with people living with their partners in the same nursing home, those who live with alone or share the room with unknown person may become more frail because of poorer social ties [32] and mental disorders [33]. In line with previous studies [34,35], we also found that regular exercise was associated with physical frailty.…”
Section: Discussionsupporting
confidence: 89%
“…The possible explanation could be that older people who had been living in a private institution (more expensive in the metropolitan areas than public institution) usually have higher social economic status; they were more likely to feel lonely [30] and loss of appetite [31] when staying away from family and changing their ways of previous life, resulting in higher likelihood of being frailer. Compared with people living with their partners in the same nursing home, those who live with alone or share the room with unknown person may become more frail because of poorer social ties [32] and mental disorders [33]. In line with previous studies [34,35], we also found that regular exercise was associated with physical frailty.…”
Section: Discussionsupporting
confidence: 89%
“…One possible explanation could be that older adults living in private institutions (more expensive in the metropolitan areas than public institutions) usually have higher social economic status, are perhaps more likely to feel more lonely [ 13 ] and suffer loss of appetite [ 33 ] when staying away from family and changing their ways of previous life, resulting in higher likelihood of being frailer. Compared with people living with their partners in the same nursing home, those who live with alone or share the room with unknown person may become more frail because of poorer social ties [ 34 ] and mental disorders [ 35 ]. In line with previous studies [ 36 , 37 ], we also found that regular exercise was associated with physical frailty.…”
Section: Discussionmentioning
confidence: 99%
“…The Tilburg Frailty Indicator (TFI) and adequately treated in order to improve people's mood and their motivation for an active life. [23][24][25] Poor social life is one of the principal reasons for low quality of life in elderly people, and loneliness seems to be an independent predictor for their functional deterioration and mortality. 22,[26][27][28][29][30] Furthermore, for the frail elderly individuals, social relationship is the most important factor for their existence, while non-frail older subjects consider health as the most critical one.…”
Section: Discussionmentioning
confidence: 99%